Urgensi Implementasi SIMKATMUH Di Majelis Pendidikan Dasar Dan Mengengah Muhammadiyah Kabupaten Cirebon - Arief Hidayat Afendi; Bella Marlianti (Jurnal PGSD, 2020)
Information systems play a role in the field of accounting because many accounting information processing systems are offered with the aim of making it easy for accountants to produce information that can be trusted, timely, complete, understandable and tested. Good or bad performance of an accounting information system can be seen from the satisfaction of users of the accounting information system itself. An information system will be successful if supported by several supporting factors.This research was conducted on employees or users associated with the implementation of accounting information systems at Muhammaidyah Charitable Enterprises in Cirebon Regency with a sample of 30 respondents. The results showed that only the formalization variable of the development of accounting information systems had significant and significant influence on the performance of accounting information systems while the other variables had no effect on the performance of accounting information systems. Keywords: Accounting information systems; Islamic Organization; Muhammaidyah Charitable Enterprises